Identification of B‐type procyanidins in Fallopia spp. involved in biological denitrification inhibition. (2nd December 2015) - Bardon, Clément; Piola, Florence; Haichar, Feth el Zahar; Meiffren, Guillaume; Comte, Gilles; Missery, Boris; Balby, Manon; Poly, Franck
Summary: Nitrogen (N) is considered as a main limiting factor in plant growth, and nitrogen losses through denitrification can be responsible for severe decreases in plant productivity. Recently, it was demonstrated that F allopia spp. is responsible for biological denitrification inhibition (BDI) through the release of unknown secondary metabolites. Here, we investigate the secondary metabolites involved in the BDI of F allopia spp. The antioxidant, protein precipitation capability of F allopia spp. extracts was measured in relation to the aerobic respiration and denitrification of two bacteria (Gram positive and Gram negative). Proanthocyanidin concentrations were estimated. Proanthocyanidins in extracts were characterized by chromatographic analysis, purified and tested on the bacterial denitrification and aerobic respiration of two bacterial strains. The effect of commercial procyanidins on denitrification was tested on two different soil types. Denitrification and aerobic respiration inhibition were correlated with protein precipitation capacity and concentration of proanthocyanidins but not to antioxidant capacity. These proanthocyanidins were B‐type procyanidins that inhibited denitrification more than the aerobic respiration of bacteria. In addition, procyanidins also inhibited soil microbial denitrification. We demonstrate that procyanidins are involved in the BDI of F allopia spp. Our results pave the way to a better understanding of plant–microbe interactions and highlight future applications for a more sustainable agriculture.